IgG4-Related Sclerosing Cholangitis: Rarely Diagnosed, but not a Rare Disease. (21st December 2021) - Drazilova, Sylvia; Veseliny, Eduard; Lenartova, Patricia Denisa; Drazilova, Dagmar; Gazda, Jakub; Grgurevic, Ivica; Janicko, Martin; Jarcuska, Peter
Abstract : IgG4-related sclerosing cholangitis, a biliary manifestation of an IgG4-related disease, belongs to the spectrum of sclerosing cholangiopathies which result in biliary stenosis. It presents with signs of cholestasis and during differential diagnosis it should be distinguished from cholangiocarcinoma or from other forms of sclerosing cholangitis (primary and secondary sclerosing cholangitis). Despite increasing information and recently established diagnostic criteria, IgG4-related sclerosing cholangitis remains underdiagnosed in routine clinical practice. The diagnosis is based on a combination of the clinical picture, laboratory parameters, histological findings, and a cholangiogram. Increased serum IgG4 levels are nonspecific but are indeed a part of the diagnostic criteria proposed by the Japan Biliary Association and the HISORt criteria for IgG4-SC. High serum IgG4 retains clinical utility depending on the magnitude of elevation. Approximately 90% of patients have concomitant autoimmune pancreatitis, while 10% present with isolated biliary involvement only. About 26% of patients have other organ involvement, such as IgG4-related dacryoadenitis/sialadenitis, IgG4-related retroperitoneal fibrosis, or IgG4-related renal lesions. A full-blown histological finding characterized by IgG4-enriched lymphoplasmacytic infiltrates, obliterative phlebitis, and storiform fibrosis is difficult to capture in practice because of its subepithelial localization. However, the histological yield is increased by immunohistochemistry, with evidence of IgG4-positive plasma cells. Based on a cholangiogram, IgG-4 related sclerosing cholangitis is classified into four subtypes according to the localization of stenoses. The first-line treatment is corticosteroids. The aim of the initial treatment is to induce clinical and laboratory remission and cholangiogram normalization. Even though 30% of patients have a recurrent course, in the literature data, there is no consensus on chronic immunosuppressive maintenance therapy. The disease has a good prognosis when diagnosed early.